2021
DOI: 10.1021/acsmedchemlett.1c00277
|View full text |Cite
|
Sign up to set email alerts
|

Lathyrane Diterpenoids as Novel hPXR Agonists: Isolation, Structural Modification, and Structure–Activity Relationships

Abstract: Pregnane X receptor (PXR) that orchestrates the intricate network of xeno- and endobiotic metabolism is considered as a promising therapeutic target for cholestasis. In this study, the human PXR (hPXR) agonistic bioassay-guided isolation of Euphorbia lathyris followed by the structural modification led to the construction of a lathyrane diterpenoid library (1–34). Subsequent assay of this library led to the identification of a series of potent hPXR agonists, showing better efficacy than that of typical hPXR ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…PXR contains a DNA‐binding domain (DBD) at the N‐terminus that facilitates binding to DNA responsive elements and a ligand‐binding domain (LBD) at the C‐terminus which is responsible for ligand binding and interaction with co‐regulators. [ 18‐19 ] Results revealed that compounds 1 , 2 and 4 were docked well into the ligand binding domain (LBD) by the establishment of multiple hydrogen bonds with residue such as HIS407, ARG410 and SRE247 and van der Waals effects (Figure 5D), which was similar to activing natural products praeruptorin A, salvianolic acid B and protocatechuic aldehyde. [ 18 ] Interestingly, the σ − π interactions with TRP299 residue were only observed in compounds 1 and 4 , and the number of hydrogen bonds and σ − π interactions may contribute to interpreting their higher affinity than 2 (–10.4, –8.4, –10.0 kcal/mol for 1 , 2 and 4 , respectively).…”
Section: Resultsmentioning
confidence: 98%
“…PXR contains a DNA‐binding domain (DBD) at the N‐terminus that facilitates binding to DNA responsive elements and a ligand‐binding domain (LBD) at the C‐terminus which is responsible for ligand binding and interaction with co‐regulators. [ 18‐19 ] Results revealed that compounds 1 , 2 and 4 were docked well into the ligand binding domain (LBD) by the establishment of multiple hydrogen bonds with residue such as HIS407, ARG410 and SRE247 and van der Waals effects (Figure 5D), which was similar to activing natural products praeruptorin A, salvianolic acid B and protocatechuic aldehyde. [ 18 ] Interestingly, the σ − π interactions with TRP299 residue were only observed in compounds 1 and 4 , and the number of hydrogen bonds and σ − π interactions may contribute to interpreting their higher affinity than 2 (–10.4, –8.4, –10.0 kcal/mol for 1 , 2 and 4 , respectively).…”
Section: Resultsmentioning
confidence: 98%
“…EFL9 (80) (Figure 8), was found to be the most active compound, this could significantly activate hPXR, as evidenced by the hPXR reporter gene activity (6.9-fold), and up-regulate the expressions of hPXR downstream key genes CYP3A4, CYP2B6, and MDR1. SAR studies revealed that acyloxy substituents on C-7, specifically a nicotinoyl group, and the presence of 14-carbonyl were essential to activity [79]. In a second study, the effects of epoxyboetirane A (11) (Figure 4) and euphoboetirane A (54) (Figure 6) on NPC proliferation was evaluated.…”
Section: Anticholestasismentioning
confidence: 99%
“…Anticholestasis Recent studies have suggested that lathyrane diterpenoids could serve as a new type of human pregnane X receptor (hPXR) agonist for future anticholestasis drug development. In a bioassay-guided isolation on E. lathyris extract looking for an hPXR agonistic compound, 16 lathyrane diterpenoids were isolated [79]. Five of them were novel compounds and were named euphlathyrinoid A-E (148-152) (Figure 27).…”
Section: Anticholestasismentioning
confidence: 99%
“… 98 It is worth mentioning that several compounds and drugs have been recently identified as selective PXR agonists, including lathyrane diterpenoids, garcinoic acid, calcium channel blocker felodipine, anti-cancer drug dabrafenib, atypical antipsychotics quetiapine and etc. 99 , 100 Unlike most of other NRs, PXR activation is species-specific due to the distinction of its LBD. In scientific field, pregnenolone-16a-carbonitrile (PCN) is a specific agonist used for activating mouse PXR, while rifampicin represents a selective agonist for human PXR.…”
Section: Pregnane X Receptor (Pxr)mentioning
confidence: 99%